The Role of E-Commerce in the Management of Online Travel Agents - Evada Rustina; Dwi Endaryanti; Ade Riawan; Hastuti Pertiwi Bima Putri; Sumarwanto (Cita konsultindo, 2023)
The rapid development of technology encourages companies, especially in the hospitality sector, to follow the online sales market, one of which is Cavinton Hotel Yogyakarta. e-Commerce is part of Electronic Business which is carried out using electronic transmission by experts and business people. The purpose of this study is to examine how the role of E-Commerce in managing online travel agents at Cavinton Hotel Yogyakarta. This research uses a qualitative approach with data collection methods including observation, interviews, documentation and literature studies. From the results of the study, it was found that the role carried out by E-Commerce in managing an online travel agent to attract customers to book rooms at Hotel Cavinton Yogyakarta By Tritama Hospitality is very influential in increasing revenue.